Frequency, Characteristics and Complications of COVID-19 in Hospitalized Infants. Issue 3 (March 2022) - Hobbs, Charlotte V.; Woodworth, Kate; Young, Cameron C.; Jackson, Ashley M.; Newhams, Margaret M.; Dapul, Heda; Maamari, Mia; Hall, Mark W.; Maddux, Aline B.; Singh, Aalok R.; Schuster, Jennifer E.; Rowan, Courtney M.; et al.
Abstract : Background: Previous studies of severe acute respiratory syndrome coronavirus 2 infection in infants have incompletely characterized factors associated with severe illness or focused on infants born to mothers with coronavirus disease 2019 (COVID-19). Here we highlight demographics, clinical characteristics and laboratory values that differ between infants with and without severe acute COVID-19. Methods: Active surveillance was performed by the Overcoming COVID-19 network to identify children and adolescents with severe acute respiratory syndrome coronavirus 2–related illness hospitalized at 62 sites in 31 states from March 15 to December 27, 2020. We analyzed patients >7 days to <1 year old hospitalized with symptomatic acute COVID-19. Results: We report 232 infants >7 days to <1 year of age hospitalized with acute symptomatic COVID-19 from 37 US hospitals in our cohort from March 15 to December 27, 2020. Among 630 cases of severe COVID-19 in patients >7 days to <18 years old, 128 (20.3%) were infants. In infants with severe illness from the entire study period, the median age was 2 months, 66% were from racial and ethnic minority groups, 66% were previously healthy, 73% had respiratory complications, 13% received mechanical ventilation and <1% died. Conclusions: Infants accounted for over a fifth of children <18 years of age hospitalized for severe acute COVID-19, commonly manifesting with respiratory symptoms and complications. Although most infants hospitalized with COVID-19 did not suffer significant complications, longer term outcomes remain unclear. Notably, 75% of infants with severe disease were <6 months of age in this cohort study period, which predated maternal COVID-19 vaccination, underscoring the importance of maternal vaccination for COVID-19 in protecting the mother and infant.